Lithium and Stannum Hybrid Anodes for Flexible Wire‐Type Lithium–Oxygen Batteries. Issue 2 (9th September 2020) - Liu, Tong; Yu, Yue; Yang, Xiao-Yang; Wang, Jin; Zhang, Xin-Bo
Abstract : Flexible lithium–oxygen batteries (LOBs) are promising candidates for next‐generation portable and flexible devices due to their ultrahigh theoretical energy density. However, the widely used metallic lithium anode leads to many obstacles that have to be surmounted when it is applied to the 1D flexible LOB. Herein, the LiSn hybrid anode that is facilely generated by molten tin solders and lithium metal is used in wire‐type LOBs to improve the wettability of molten Li against Cu current collectors, increase the strength of anode, and repress the growth of dendrites. This anode cycles stably for more than 1000 h at the current density of 5 mA cm −2 with minimal voltage divergence. The obtained wire‐type LOB composed of this LiSn hybrid anode, flexible gel–polymer electrolyte, and carbon thread cathode exhibit a higher specific capacity, stable reversibility, superior structure flexibility, and cycling stability (up to 247 cycles). Utilizing the tin solders to fabricate the LiSn hybrid anode not only decreases the fabrication cost but also simplifies the production procedures of flexible wire‐type LOBs, providing new ideas for environmental protection and practical applications. Abstract : A flexible/wearable wire‐type lithium–oxygen battery based on LiSn hybrid anode for flexible electronics is provided. Due to the close affinity to copper, high strength, and inhibition of dendrite, the linear LiSn hybrid anode displays a long cycle life. Combined with free‐standing gel–polymer electrolyte and high‐efficiency Ru–Super P (SP) cathode, the battery demonstrates excellent flexibility and electrochemical performances.